PENINGKATAN PENDAPATAN PETANI PADI RAWA PASANG SURUT MELALUI PENERAPAN TEKNOLOGI RAISA DI SUMATERA SELATAN - Widyantoro Widyantoro; N. Agustiani; A. Ruskandar (Agroswagati Jurnal Agronomi, 2019)
Tidal swamp land has great potential and opportunities to be used as food production areas, especially rice. The IAARD has produced many technologies and varieties that are adaptive in the growing environment of tidal swamps, but their use and distribution have not been widely known and applied by farmers. The research to increase the income of tidal swamp rice farmers is intended to analyze the tidal swamp rice technology that is being developed. Research in Sukamulya Village, sub district Tungkal Ilir, District of Banyuasin, South Sumatera. The research on 2018 dry season, activities began with a pre-survey which was also used to conduct needs and opportunity studies on farmer groups who would apply tidal swamp rice cultivation technology to tidal swamp rice activities using the RAISA technology approach. Data collection is done using with and without method by means of farm record keeping. Farming analysis is used to analyze collected data. Pre-survey results, based on ranking and priority, there are 5 problems that must be immediately implemented and addressed, namely substandard irrigation, rat control, weed control, drought in the constitutional court, and fertilizer dosage. Based on the agreement, the 5 problems will be overcome by mutual cooperation on the cleaning of tertiary channels, integrated rate control, integrated weed control, planting on time, the use of water pumps, rice variety tolerant to drought, and applying fertilizer doses based on kid fertilizer. The average grain yield of farmers cooperator in tidal swamp rice farms of 5,420 kg/ha is 18.86% higher than that of non-cooperator farmers who average 4,560 kg/ha and the level of profit from tidal swamp farming in farmers cooperator is more feasible when compared to non-cooperator farmers.